Communication difficulties among individuals with hearing impairments during the COVID-19 pandemic and their associated factors: a cross-sectional study using a national survey in Japan - Taeko Watanabe; Takehiro Sugiyama; Ai Suzuki; Nanako Tamiya (BMC Public Health)
Abstract Background The COVID-19 pandemic and the widespread use of face masks have exacerbated communication challenges, especially among individuals with hearing impairments. This study aimed to identify the factors influencing interpersonal communication difficulties among individuals with hearing impairment in Japan during the pandemic. Methods This cross-sectional study examined data from the 2022 Survey on Difficulty in Living. The study focused on individuals aged 12 years and older who held physical disability certificates for hearing impairments. The outcome was difficulties with interpersonal communication, with the primary factor of interest being the presence of a regular caregiver and the use of voice recognition software. Additional factors examined included sex, age, degree of hearing impairment, age at first hearing impairment certification, and the frequency of outings. Results Among 410 individuals with hearing impairments, 55.6% experienced communication difficulties during the COVID-19 pandemic. Multivariable analysis indicated that individuals with regular caregivers were less likely to experience communication difficulties (adjusted prevalence ratio (aPR) = 0.81, 95% confidence interval (CI): 0.66–0.99), while those using voice recognition software were more likely to face difficulties (aPR = 1.37, 95% CI: 1.04–1.80). In addition, individuals aged 40–64 years and those with more severe hearing impairment (Grade 2–4) were more likely to experience communication difficulties. Frequent outings were also associated with an increased likelihood of communication difficulties (aPR = 1.28, 95% CI: 1.03–1.58). Conclusions During emergencies such as the COVID-19 pandemic, self-reliant individuals with hearing impairments may require increased public support to mitigate communication barriers.